Systematic Literature Review: Implementation of Mobile Banking - Sisi Maghfirah Rahmah Sembiring; Sambas Ade Kesuma; Risanty; Muhammad Simba Sembiring (PT FORMOSA CENDEKIA GLOBAL, 2023)
The main purpose of SLR is to answer the RQ with the results of previous studies as evidence that has been identified, assessed, and interpreted. The RQs on SLR identify the significant journals, the most influential researchers, topics, methods, and theories. Based on inclusion and exclusion criteria, 20 papers indexed by Scopus were obtained that discuss the implementation of mobile banking, with publication years ranging from 2010 to 2021. The implementation of mobile banking focuses on six topics. The most widely used method is survey research with a cross-sectional design. While TAM is the most commonly used theory, the SLR outlines implications that can assist practitioners in surmounting the deceleration issue in implementing mobile banking and preparing for the cashless era in Indonesia.